An Overview of the Canine Estrous Cycle - Zabuli , Jahid (Journal of Natural Sciences – Kabul University, 2022)
Bitches generally reach puberty between 6 and 12 months of age, although the range can vary from four to twenty-four months depending on the breed. Smaller breeds reach adult size earlier and thus attain puberty sooner than larger breeds. The first estrus can sometimes be abnormal, appearing as prolonged or split estrus. It tends to occur earlier when young bitches are housed with mature, cycling bitches. Estrus cycles occur year-round, with a slight increase in late winter and early spring. The interval between estrous cycles averages approximately six months, ranging from four to twenty-four months. Clinical evaluations to determine the stage of the estrous cycle include behavioral observations, vulvar and vaginal appearance, vaginal cytology, uterine tone, and the measurement of progesterone and luteinizing hormone concentrations.